2003
DOI: 10.1029/2003ja009936
|View full text |Cite
|
Sign up to set email alerts
|

Sublimation of ice particles from rocket exhausts in the upper atmosphere

Abstract: .[1] The process of sublimation of ice particles from a rocket exhaust in the upper atmosphere is examined. Heating by solar radiation and losses of energy by means thermal radiation and sublimation are taken into account in the thermal balance of the ice particles. The time dependences of size and temperature of the ice particles are obtained. An estimation of water vapor concentration around the rocket trajectory is made. The process of sublimation of the rocket exhaust ice particles may be important for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Embedded inside the V‐shape enhancement region are the rTEC depletions, and they are previously known to be formed mainly by the neutral molecule of rocket exhaust plumes (i.e., water and ice particles) that rapidly decrease the ionospheric plasma through the much faster dissociative recombination processes [cf. Karlov et al ., ; Platov and Kosch , ; Mendillo et al , ; Furuya and Heki , ]. More than 10 min after rocket passage, there are delayed disturbance waves propagating outward from the east side of the V‐shape structure (denoted by red dashed curves in Figures d–e).…”
Section: Gps‐tec Observations Of February 2016 North Korea Rocket Launchmentioning
confidence: 98%
“…Embedded inside the V‐shape enhancement region are the rTEC depletions, and they are previously known to be formed mainly by the neutral molecule of rocket exhaust plumes (i.e., water and ice particles) that rapidly decrease the ionospheric plasma through the much faster dissociative recombination processes [cf. Karlov et al ., ; Platov and Kosch , ; Mendillo et al , ; Furuya and Heki , ]. More than 10 min after rocket passage, there are delayed disturbance waves propagating outward from the east side of the V‐shape structure (denoted by red dashed curves in Figures d–e).…”
Section: Gps‐tec Observations Of February 2016 North Korea Rocket Launchmentioning
confidence: 98%
“…Platov and Kosch [] comprehensively considered the thermal balance of ice particles in the upper atmosphere and demonstrated that the sublimation time of ice particles explains the formation of a large‐scale gas‐dust cloud around the rocket trajectory at radial distances up to 200–300 km. Platov et al .…”
Section: Introductionmentioning
confidence: 99%
“…12 Optical phenomena associated with gas formations containing ice particles have been observed at high altitudes. 3,13 Reference 3 suggests that similar optical phenomena might develop also at lower altitudes ∼150 km, but could be hidden by the luminosity of twilight or other brighter optical formations. We suggest that if a dusty plasma instability can occur, perhaps radar backscattering from the unstable waves might be a diagnostic of such artificial ice particles clouds at lower altitudes.…”
Section: Numerical Results and Applicationsmentioning
confidence: 96%
“…We suggest that radar backscatter from such unstable waves, which propagate perpendicular to the magnetic field, might have application as a diagnostic for lower-altitude ice/dust-gas formations arising from rocket exhaust. 3,13 We note, however, that we have used sets of nominal background plasma parameters and possible dust parameters. Further work should include more detailed evaluations involving ranges of gas, dust, and plasma parameters that might occur in such rocket exhaust clouds at different altitudes.…”
Section: Discussionmentioning
confidence: 99%